2010
DOI: 10.1074/jbc.m109.086843
|View full text |Cite
|
Sign up to set email alerts
|

The Contact Region between Three Domains of the Extracellular Loop of ASIC1a Is Critical for Channel Function

Abstract: Acid-sensing ion channels are members of the epithelial Na ؉ channel/degenerin family. They are neuronal nonvoltage-gated Na ؉ channels that are activated by extracellular acidification. In this study, we investigated the role of a highly conserved region of the extracellular part of ASIC1a that forms the contact between the finger domain, the adjacent ␤-ball, and the upper palm domain in ASIC1a. The finger domain contributes to the pH-dependent gating and is linked via this contact zone to the rest of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Although its mutation to Asn did not affect ASIC pH dependence (23), we recently observed that its mutation to Cys and subsequent sulfhydryl modification almost completely suppressed ASIC current, suggesting that His-163 is important for ASIC function, although likely not as pH sensor (46).…”
Section: Discussionmentioning
confidence: 99%
“…Although its mutation to Asn did not affect ASIC pH dependence (23), we recently observed that its mutation to Cys and subsequent sulfhydryl modification almost completely suppressed ASIC current, suggesting that His-163 is important for ASIC function, although likely not as pH sensor (46).…”
Section: Discussionmentioning
confidence: 99%
“…As the simplest ligand possible, whether H ϩ gates ASICs by titration of a single or multiple polar residues remains controversial (24). In recent years, multiple putative pH sensors have been proposed (4,7,8,24,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), e.g. the residues located in the cleft between the thumb and finger domains (4); residues around Glu-79 and Glu-423 in the palm domain (4,7,40); a cluster of acidic residues in the post-TM1 and pre-TM2 regions (Glu-63, His-72/ His-73, and Asp-78 of ASIC1a) (24,41).…”
Section: Discussionmentioning
confidence: 99%
“…Kellenberger and co-worker have shown that some residues belonging to the upper palm domain form a contact with the finger and the adjacent ␤-ball in ASIC1a (33). They have demonstrated that this zone undergoes conformational changes during inactivation and that chemical modification of this contact region decreases the probability of channel opening.…”
Section: The Finger/palm/␤-ball Connecting Domain (Domain P) and The mentioning
confidence: 99%